POLITIK HUKUM KESETARAAN KAUM PEREMPUAN DALAM ORGANISASI MASYARAKAT ISLAM DI INDONESIA - Asnawi, Habib Shulton (Musawa Jurnal Studi Gender dan Islam, 2012)
In the normative level, generally all agreed to place women are equal to men, that is the position as humans, as well as the servant of Allah. Women are recognized to have a number of rights and freedoms, including the right to engage in politics, especially in the organization of the Islamic society. To strengthen the protection of women's rights, the government of Indonesia to make a policy or legislation (political law), both to improve policies of national legislation and policies ratified international law. However, when the policy (political law) or a pattern of gender relations between men and women drawn into operational a practical level, it appears that a long debate and a serious problem occurs. The rights of women experiencing prolonged discrimination, discrimination and marginalization occurs at the level of political rights and policies in the organization of Islamic society. In Indonesia, the rights of women in Islamic society organization, still have enough depth concerns. The pro and contra related to gender equality in Indonesia, particularly in the field of Islamic society organizations would affect the wheels of government in Indonesia, particularly in relation to the State of trademark law is the protection and freedom of human rights. Therefore, policies need to be related to equality between men and women both fair and legal.